Game Theory : A Non-Technical Introduction To The Analysis of Strategy - McCain, Roger A. (Thomson South Western, 2004)
Game theory is a field of study that was developed in the latter half of the twentieth century. Today, more than ever before. game theory attracts attention for its wide range of applications ranging from business, auctions, and elections to military strategy, biology, and gambling.